Epigenetic disorders: Lessons from the animals–animal models in chromatinopathies - Di Fede, Elisabetta; Grazioli, Paolo; Lettieri, Antonella; Parodi, Chiara; Castiglioni, Silvia; Taci, Esi; Colombo, Elisa Adele; Ancona, Silvia; Priori, Alberto; Gervasini, Cristina; Massa, Valentina (Frontiers in Cell and Developmental Biology, 2022)
Chromatinopathies are defined as genetic disorders caused by mutations in genes coding for protein involved in the chromatin state balance. So far 82 human conditions have been described belonging to this group of congenital disorders, sharing some molecular features and clinical signs. For almost all of these conditions, no specific treatment is available. For better understanding the molecular cascade caused by chromatin imbalance and for envisaging possible therapeutic strategies it is fundamental to combine clinical and basic research studies. To this end, animal modelling systems represent an invaluable tool to study chromatinopathies. In this review, we focused on available data in the literature of animal models mimicking the human genetic conditions. Importantly, affected organs and abnormalities are shared in the different animal models and most of these abnormalities are reported as clinical manifestation, underlying the parallelism between clinics and translational research.